CUSTOMER RELATIONSHIP MANEGEMENT SEBAGAI STRATEGI RELASIONAL UMKM: STUDI KASUS PADA CAFE ABANG - Hasan, Golan; Kavitan, Vebbie; Waty, Indah; Steven, Steven; Gautama, Jocky; Jesslieca, Jesslieca (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This study aims to describe the implementation of customer relationship management in the culinary-based SME Cafe Abang and evaluate its influence on service quality, customer satisfaction, and customer loyalty. The research applies a qualitative descriptive approach through field observation and in-depth interviews with the business owner. The findings indicate that Cafe Abang intuitively applies CRM through personalized service, a comfortable atmosphere, and consistent communication. Customers respond to this approach with emotional satisfaction and demonstrate loyalty through repeat visits and word-of-mouth recommendations. Service quality emerges as a key element in fostering sustainable relationships, even without formal digital systems. Experience-based CRM practices are proven effective in generating customer loyalty in the context of Small and Medium Enterprises (SMEs). This study confirms that relational strategies focusing on emotional closeness and service consistency can shape loyalty without relying on advanced technology.